Single Nucleotide Polymorphisms of Porcine lncMGPF Regulate Meat Production Traits by Affecting RNA Stability - Lv, Wei; Zhao, Shiyu; Hou, Yunqing; Tong, Qian; Peng, Yaxin; Li, Jianan; Xu, Zaiyan; Zuo, Bo (Frontiers in Cell and Developmental Biology, 2021)
lncMGPF is a novel positive regulator of myogenic differentiation, muscle growth and regeneration in mouse, pig, and human. But whether natural mutations within lncMGPF gene regulate animal meat production traits is unclear. In this study, ten single nucleotide polymorphisms (SNPs) of pig lncMGPF (plncMGPF) gene were identified among commercial pig breeds and Chinese local pig breeds. These SNPs are highly linked and constructed into multiple haplotypes, and haplotype ATTCATGTTC (H1) mainly exists in commercial pig breeds while haplotype GCCTGCACCT (H3) is more frequent in Chinese local pig breeds. Association analysis indicated that all SNPs are significantly associated with the backfat thickness and loin muscle area (P < 0.05), respectively, and homologous H1 individuals have higher loin muscle area and lower backfat thickness than H3 pigs. Bioinformatics and functional analysis showed that haplotype H1 has a longer half-life and more stable RNA secondary structure than haplotype H3. plncMGPF haplotype H1 has stronger effects on pig primary myogenic progenitor cells differentiation and muscle growth than haplotype H3. Further experiments showed that two SNPs (rs81403974 and rs325492834) function together to confer plncMGPF stability and function. Our observation suggested that the SNPs in lncMGPF can change the RNA stabilities and lncMGPF function, thereby affecting the porcine meat production traits.